METHODOLOGY FOR DEVELOPING INFORMATION-ANALYTIC COMPETENCY OF FUTURE PRIMARY CLASS TEACHERS - Furkat Zakirov,; Khamrakul Sanakulov,; Sobirjon Meyliev,; Rozimurod Abiev,; Ziyamuhammad Nematov, (The Bioscan, 2024)
In modern conditions of the emergence of a global information society, the role of information in the training of a future specialist is significantly increasing. The idea is increasingly gaining ground in people's minds that the future strategic potential of society will not be energy resources, but information and scientific knowledge. Information becomes the main resource for the scientific, technical, and socio-economic development of society, significantly influences the accelerated development of science, technology, and various industries, and plays a significant role in the process of modernization of education.